Addressing fouling build-up through advanced coatings. (September 2013) - Davison, C; Durand, G; Taylor, A
Abstract : The industrial need for anti-fouling coatings is significant and continues to grow. Whilst applications are enormously diverse; ranging from blades on gas and wind turbines to ship hulls, and from aircraft wings to the inside of oil pipelines; one factor remains constant – the challenge of producing a coating which is both anti-fouling and durable. Many commercially available products offer anti-fouling characteristics or durability, but not both. Some of the best performing options are based on fluorine chemistry and with legislative pressure likely to constrain the application of fluorinated materials, a new breed of hybrid materials is now emerging. TWI has been developing class leading solutions in this area. This article compares commercially available products and introduces an approach to testing that enables anti-fouling characteristics to be examined against the degree of mechanical damage. Results indicate that products with high initial anti-fouling characteristics tend to degrade faster when exposed to abrasion. This emphasises the need to select the right coating for the right application.